Opposing aftereffects between a White male face set and a diverse face set. (January 2023) - Foglia, Victoria; Rutherford, M.D.
Opposing aftereffects have been observed for faces categorized by gender, race, and age. In order to form opposing aftereffects, it appears that the two face sets must be both physically distinct and differ in terms of social meaning. The current study tests whether (1) a face set that is diverse with respect to sex and race can produce a coherent aftereffect and (2) whether this diversity itself is socially meaningful enough to support opposing aftereffects. Participants adapted to a homogenous face set consisting of only White male Republican congressmen and a diverse face set consisting of White, Asian, Black, and Latino male and female Democratic congress members. Opposing aftereffects were observed: participants adapted simultaneously and in opposite directions to the face sets. These results are the first evidence of adaptation to a face set that varies based on race and sex, and the first evidence of diversity being perceived as a socially meaningful category marker.